Scorpion venom peptides enhance immunity and survival in Litopenaeus vannamei through antibacterial action against Vibrio parahaemolyticus - Zeng, Ling; Sun, Yulin; Zhang, Hualin; Yi, Xiangxi; Du, Ran; Chen, Ziming; Wang, Qi (Frontiers in Immunology, 2025)
IntroductionScorpion venom-derived antimicrobial peptides (AMPs) have emerged as promising candidates for combating bacterial infections owing to their potent activity and unique mechanisms of action. This study focuses on three 13-amino-acid peptides—BmKn1, BmKn2, and BmKn2-7—derived from the venom of Mesobuthus martensii. The aim is to elucidate their structural features, antibacterial efficacy, and immunomodulatory effects in Litopenaeus vannamei infected with Vibrio parahaemolyticus (VP).MethodsThe peptides were synthesized and comprehensively characterized for their amphipathic α-helical structures, net charges, and hydrophobicity. Their antibacterial mechanisms were investigated using a series of assays, including membrane permeability (inner/outer membrane disruption), membrane depolarization, reactive oxygen species (ROS) quantification, and ATPase activity measurement. In vivo challenge experiments were conducted to evaluate survival rates in L. vannamei infected with VP. Additionally, immune enzyme activities (phenoloxidase [PO], complement component 3 [C3]) and inflammatory/antimicrobial gene expression levels (TNF-α, IL-1β, TGF-β, ALF, Crus) were analyzed. Furthermore, intestinal transcriptome profiling was performed to identify the activated immune pathways.ResultsAll peptides exhibited membrane-targeting activity: BmKn2-7 showed superior outer membrane penetration and depolarization, while BmKn1 was more effective in inner membrane disruption and ROS induction. In vivo, all peptides significantly improved survival rates in VP-infected shrimp (P < 0.01), with BmKn2-7 ≈ BmKn1 > BmKn2 in efficacy. Immune modulation was evident through increased PO and C3 activity (P < 0.05) and reduced expression of inflammatory cytokines and antimicrobial genes (P < 0.05). Transcriptome analysis revealed BmKn2-7 activated PPAR, AMPK, and FoxO signaling pathways.DiscussionThe amphipathic α-helical structure of these peptides is fundamental to their membrane-disruptive activity. The enhanced outer membrane targeting of BmKn2-7 likely correlates with structural modifications that optimize hydrophobicity and charge distribution. The differential efficacy in immune regulation, such as BmKn2-7's broad pathway activation versus BmKn1's selective ROS induction, indicates structure-dependent functional divergence. These findings highlight the potential of tailored scorpion venom peptides as dual-action agents against bacterial infections and immune dysregulation